2017
DOI: 10.1371/journal.pone.0171036
|View full text |Cite
|
Sign up to set email alerts
|

Expression and prognostic significance of zinc fingers and homeoboxes family members in renal cell carcinoma

Abstract: Zinc fingers and homeoboxes (ZHX) is a transcription repressor family that contains three members; ZHX1, ZHX2, and ZHX3. Although ZHX family members have been associated with the progression of cancer, their values as prognostic factors in cancer patients have been poorly examined. Renal cell carcinoma (RCC) is a highly heterogeneous, aggressive cancer that responds variably to treatment. Thus, prognostic molecular markers are required to evaluate disease progression and to improve the survival. In clear cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 18 publications
0
30
0
Order By: Relevance
“…However, another report revealed that ZHX2 protein expression was observed only in cancer tissues and associated with advanced clinical stage and metastasis of hepatocellular carcinoma 43. Another recent study showed downregulated ZHX3 expression and upregulated ZHX2 expression in renal cell carcinoma, and the expression levels of ZHX1 and ZHX3 were significantly associated with pathological stage 32. Decreased ZHX2 expression has also been found to be correlated with an unfavorable outcome in multiple myeloma 44.…”
Section: Discussionmentioning
confidence: 96%
“…However, another report revealed that ZHX2 protein expression was observed only in cancer tissues and associated with advanced clinical stage and metastasis of hepatocellular carcinoma 43. Another recent study showed downregulated ZHX3 expression and upregulated ZHX2 expression in renal cell carcinoma, and the expression levels of ZHX1 and ZHX3 were significantly associated with pathological stage 32. Decreased ZHX2 expression has also been found to be correlated with an unfavorable outcome in multiple myeloma 44.…”
Section: Discussionmentioning
confidence: 96%
“…Decreased expression of ZHX2 in Hodgkin lymphoma is associated with a translocation between chromosomes 4q27 and 8q24, the location of ZHX2. 47 Of particular interest are the mechanisms by which ZHX2 expression is inhibited in HCC. 46 In contrast, ZHX2 appears to be higher expressed in renal cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…46 In contrast, ZHX2 appears to be higher expressed in renal cell carcinoma. 47 Of particular interest are the mechanisms by which ZHX2 expression is inhibited in HCC. One study observed ZHX2 promoter hypermethylation and reduced ZHX2 levels in HCC, 20 indicating epigenetic regulation of ZHX2.…”
Section: Discussionmentioning
confidence: 99%
“…Zinc finger and homeoboxes 2 (ZHX2) is also a liver-enriched transcriptional repressor in adult hepatocytes and a tumor suppressor [265,266]. It is important for hepatocyte gene regulation and liver development and plays roles in renal cancer and stem cell differentiation [267][268][269][270]. ZHX2 contains four homeodomains and two C2H2 zinc finger motifs that allow for DNA binding causing transcriptional repression as both a homodimer ( Figure 3F) or a heterodimer when bound with ZHX1 [265,271].…”
Section: Zinc Finger and Homeoboxesmentioning
confidence: 99%